Application of Democratic Leadership Style to Improve Teacher Performance at SDN Manggahang 02 Bandung - Ila Aisyah; Ujang Cepi Barlian; Dahlia Puspitasari; Teri Yanto (al-Afkar, Journal For Islamic Studies, 2023)
This research has a background problem, namely How to Implement Democratic Leadership in Improving Teacher Performance at SD Negeri 02 Manggahang. well, not maximizing influence and directing teachers in carrying out their duties. As a leader, you must also be able to mobilize and influence other people to realize the vision and mission of the school together. In addition, as a democratic leader must be able to understand the condition of teachers, employees and students, also be able to communicate both orally and in writing. Democracy must also be able to make good decisions regarding internal and external affairs. This study used a qualitative approach with the subject of the principal, teachers and participants at SD Negeri 02 Manggahang. Data collection is done through passive observation, interviews, and documentation. Meanwhile, data analysis used descriptive qualitative data analysis. The results of the study show that the application of democratic leadership by the head of SDN Manggahang 02 Bandung Regency can increase teacher performance both in preparation for administrative competence and teacher professionalism, the use of methods used by teachers is also more varied, discipline also increases.